PENGARUH SOFT SKILLS TERHADAP KESIAPAN KERJA PADA MAHASISWA PENDIDIKAN IPS UNIVERSITAS NEGERI SURABAYA - Nur Hany Annisa; Nuansa Bayu Segara; Sukma Perdana Prasetya; Hendri Prastiyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the importance of mastering soft skills in increasing students' work readiness in the midst of the increasingly competitive demands of the world of work. The purpose of this study is to analyze the influence of communication skills, teamwork, adaptation, problem-solving, and work ethics on the work readiness of social studies education students of the State University of Surabaya. The approach used is quantitative with the survey method. The research sample amounted to 200 active students of the Social Studies Education Study Program, State University of Surabaya, class of 2022 and 2023, who were selected using purposive sampling techniques. Data was collected through questionnaire deployment and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 4.0. The results of the study showed that the level of student job readiness was in the medium category of 69.9% and the research model had met the Goodness of Fit criteria. In addition, communication skills, teamwork, adaptation, problem-solving, and work ethics have been proven to have a positive and significant effect on student work readiness. The findings show that the mastery of soft skills contributes to increasing the work readiness of social studies education students at the State University of Surabaya.